Thermally Stable Transparent Resistive Random Access Memory based on All-Oxide Heterostructures - Shang, Jie; Liu, Gang; Yang, Huali; Zhu, Xiaojian; Chen, Xinxin; Tan, Hongwei; Hu, Benlin; Pan, Liang; Xue, Wuhong; Li, Run-Wei (Advanced functional materials, 2014)
An all‐oxide transparent resistive random access memory (T‐RRAM) device based on hafnium oxide (HfOx) storage layer and indium‐tin oxide (ITO) electrodes is fabricated in this work. The memory device demonstrates not only good optical transmittance but also a forming‐free bipolar resistive switching behavior with room‐temperature ROFF/RON ratio of 45, excellent endurance of ≈5 × 107 cycles and long retention time over 106 s. More importantly, the HfOx based RRAM carries great ability of anti‐thermal shock over a wide temperature range of 10 K to 490 K, and the high ROFF/RON ratio of ≈40 can be well maintained under extreme working conditions. The field‐induced electrochemical formation and rupture of the robust metal‐rich conductive filaments in the mixed‐structure hafnium oxide film are found to be responsible for the excellent resistance switching of the T‐RRAM devices. The present all‐oxide devices are of great potential for future thermally stable transparent electronic applications. ITO/HfOx/ITO structure is fabricated with promising optical transmittance. The all‐oxide device demonstrates forming‐free resistive switching behaviors that are stable over a wide temperature range. The electrical switching of the transparent devices is attributed to the field‐induced formation and rupture of metal‐rich conductive filaments across the mixed‐structure hafnium oxide thin film, and are of great potential for thermally stable transparent electronic applications.